Effect of SecB chaperone on production of periplasmic penicillin acylase in Escherichia coli - Chou, C. P.; Tseng, J. H.; Kuo, B. Y.; Lai, K. M.; Lin, M. I.; Lin, H. K. (Biotechnology Progress, 1999)
The effect of SecB chaperone on production of periplasmic penicillin acylase (PAC) in Escherichia coli was investigated. It appears that formation of PAC required the function of SecB chaperone and the amount of SecB required was at a basal level. The secB mutant was defective in production of PAC, and the impairment could be complemented by extrachromosomally supplementing SecB in trans. The function of SecB might be primarily stabilizing the cytoplasmic PAC precursors. Overproduction of SecB chaperone usually resulted in an increase in the amount of PAC precursors without enhancing PAC activity. In addition, most of the PAC precursors were located in the periplasm, suggesting that formation of active PAC was likely limited by periplasmic processing steps.